A 2006 social accounting matrix for Nigeria: Methodology and results - Nwafor, Manson; Diao, Xinshen; Alpuerto, Vida (International Food Policy Research Institute, 2010)
The 2006 Nigeria SAM was built for the dynamic CGE (DCGE) model that examined the agriculture growth and investment options for reducing poverty in the country. This report provides a detailed description of this SAM, while the DCGE analysis using the SAM can be found in Diao et al. (2010).